Dichloroacetate prevents restenosis in preclinical animal models of vessel injury - Deuse, Tobias; Hua, Xiaoqin; Wang, Dong; Maegdefessel, Lars; Heeren, Joerg; Scheja, Ludger; Bolanos, Juan P.; Rakovic, Aleksandar; Spin, Joshua M.; Stubbendorff, Mandy; Ikeno, Fumiaki; Laenger, Florian; et al. (Nature, 2014)
Despite the introduction of antiproliferative drug-eluting stents, coronary heart disease remains the leading cause of death in the United States. In-stent restenosis and bypass graft failure are characterized by excessive smooth muscle cell (SMC) proliferation and concomitant myointima formation with luminal obliteration. Here we show that during the development of myointimal hyperplasia in human arteries, SMCs show hyperpolarization of their mitochondrial membrane potential (??m) and acquire a temporary state with a high proliferative rate and resistance to apoptosis. Pyruvate dehydrogenase kinase isoform 2 (PDK2) was identified as a key regulatory protein, and its activation proved necessary for relevant myointima formation. Pharmacologic PDK2 blockade with dichloroacetate or lentiviral PDK2 knockdown prevented ??m hyperpolarization, facilitated apoptosis and reduced myointima formation in injured human mammary and coronary arteries, rat aortas, rabbit iliac arteries and swine (pig) coronary arteries. In contrast to several commonly used antiproliferative drugs, dichloroacetate did not prevent vessel re-endothelialization. Targeting myointimal ??m and alleviating apoptosis resistance is a novel strategy for the prevention of proliferative vascular diseases.
EVALuna2:25471